2018
DOI: 10.1021/jacs.8b06957
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrothiolation: Regio- and Enantioselective Coupling of Thiols and Dienes

Abstract: We report a Rh-catalyzed hydrothiolation of 1,3-dienes, including petroleum feedstocks. Either secondary or tertiary allylic sulfides can be generated from the selective addition of a thiol to the more substituted double bond of a diene. The catalyst tolerates a wide range of functional groups, and the loading can be as low as 0.1 mol %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 55 publications
(27 reference statements)
0
60
0
Order By: Relevance
“…2, entry 10). Interestingly, after a thorough re-evaluation of the reaction parameters, we were able to change the thiolation site to the terminal position 5460 to generate a very good yield of the linear thioether as a single isomer (Fig. 2, entry 11).
Fig.
…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…2, entry 10). Interestingly, after a thorough re-evaluation of the reaction parameters, we were able to change the thiolation site to the terminal position 5460 to generate a very good yield of the linear thioether as a single isomer (Fig. 2, entry 11).
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…2 and Fig. 10b, the current benzylic regioselectivity can also be switched to a terminal site to form the anti -Markovnikov hydrothiolation 5460 products. A series of terminal alkenes can be effectively hydrothiolated under a modified reaction conditions ( 8a – 8d ).…”
Section: Discussionmentioning
confidence: 98%
“…Encouraged by this result and given the vital role of ligands in transition metal catalyzed transformations,w en ext interrogated as eries of commercially available ligands to improve the reaction efficiency.N otably,a8 5% yield of the desired product was obtained when the bidentate and electron-rich phosphine ligand dmpe [1,2-bis(dimethylphosphino)ethane]w as used (entry 4), while the other phosphine-, nitrogen-containing and/or N-heterocyclic carbene (NHC) ligands were found to be inferior for this transformation, leaving most of the starting 1,3-diene unreacted (entries 2-12). Further investigation of several common ruthenium(II) catalysts showed that comparative selectivity and yields could be achieved (entries [13][14][15]. Al ook at the bases revealed that t BuOLi gave the best results (entries [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…[12] In other words,a tl east six different regioisomers can be potentially formed during the addition of NuÀHacross aterminal diene,and the selectivity of the newly formed bonds depends on either the Markovnikov or anti-Markovnikov selectivity for internal addition, terminal 1,2addition, or conjugate 1,4-addition (Scheme 1a). [13][14][15][16] Recently our group [17] and that of Zhou [18] independently communicated an ickel-catalyzed 1,2-Markovnikov hydroalkylation [19] of 1,3-dienes with umpolung carbonyls to generate branched allylic compounds (Scheme 1b). In these reactions,anickel hydride species is generated and reacts with the diene to generate an electrophilic nickel-p-allyl intermediate (hydride adds preferentially to the less sterically hindered terminal olefinic carbon center;S cheme 1c,l eft).…”
Section: Introductionmentioning
confidence: 99%
“…. ) are very often applied as catalyst precursors in homogeneous catalysis [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. These coordination compounds are usually not commercially available and must therefore be synthesized.…”
Section: In Situ Generation Of Precatalystsmentioning
confidence: 99%